A critical examination of the false hope harms argument. (7th December 2020) - Bobier, Christopher A.
Abstract: Marleen Eijkholt presents a new argument in healthcare ethics, the false hope harms (FHH) argument. In brief, false hope promotes a host of individual harms (e.g., financial, physical, and psychological harms) and system‐level harms (e.g., distrust of medical practitioners, increased complexity of care and the associated costs), all of which provide reason for healthcare providers to stop promoting false hope in medicine. The goal of this paper is to show that the FHH argument is unsuccessful.